FAKTOR–FAKTOR YANG MEMPENGARUHI TERJADINYA KENAKALAN REMAJA - Riamah, Elfa Zuriana (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Juvenile delinquency is a behavior carried out by teenagers by ignoring the social valuesthat apply in society. Juvenile delinquency encompasses all behaviors that deviate from thenorms and laws of teenagers. This behavior can harm himself and the people around him.Based on data from the Metro Jaya Regional Police of Pekanbaru in 2015 the number ofjuvenile delinquency did increase from year to year, the purpose of this study was to findout